Fertility and female labor supply in Uruguay: An Economic Approach - Pagano, Juan Pablo; Rijo, Natalia; Rossi, Máximo (Población y Salud en Mesoamérica, 2010)
In the present work we study the joint determinants of fertility and female labor supply decisions in Uruguayan households. Basing on data from the Survey on Family Situation and Social Performance (Encuesta sobre Situaciones Familiares y Desempeños Sociales en Montevideo y Área Metropolitana) of 2001, we estimate the joint probability of a woman being employed and having had a child in the two years preceding the survey, through a bivariate probit model. The results confirm the existence of endogeneity between both outcomes, suggesting the presence of unobservable that make those women more prone to be in the labor force, also less prone to giving birth to children in the period. After accounting for this phenomenon, the direction of the effect under study changes.